Immune hemolysis secondary to injection of contrast medium. Issue 9 (28th August 2018) - Maurin, Carole; Vassal, Olivia; Darien, Marie; Raba, Michel; Allaouchiche, Bernard; Piriou, Vincent
Abstract : BACKGROUND: Drug‐induced immune hemolytic anemia (DIIHA) is a rare but sometimes severe side effect. CASE REPORT: We describe the case of a 32‐year‐old patient who presented a cardiovascular collapse and a severe hemolysis secondary to the injection of iomeprol, a contrast medium, after a carcinologic surgery. RESULTS: The evolution was favorable after blood transfusion and short catecholamine support. The biology showed drug‐dependent antibodies after incubation with iomeprol. CONCLUSION: This case is the second report of DIIHA with iomeprol.